Barriers to Social Integration of Muslims In Europe From the Perspective of Murad Hoffmann - Assiri, Ahmed Ibrahim; Abdul Hamid, Faisal Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2017)
Political Systems In The West Have Made Great Efforts In Order To Dissolve The Identity Of Muslims In Western Society, So The Muslim Becomes A Copy Of The Moroccan Citizen Which Does Not Give The Church And Anglican Education Attention .Christian Religious Values Do Not Constitute A Handicap And Exercise His Life As He Wishes ,Despite That Many Muslims Living In The West Still Struggle To Live With Western Societies , While Remaining As Much As Possible On The Islamic Identity. In Return, They Face Many Religious, Social and Political Problems. In This Article, I Will Highlight Some of The Problems Muslims Face In the West from Murad Hoffmann’s Point of View. The Importance of Hoffman’s View Is That He Is One of The Orientalists Whom God Guided to Islam. In Addition to Being German Origin and Origin, This Gives His Opinion A Lot of Importance and Depth Because He Lived the Experience of Residence in The West Christian And Then Muslim